Recrudescence of transmission of onchocerciasis in some endemic communities in Kaduna State, Nigeria: What is the way forward? - Timothy O Olanrewaju; Felicia N C Enwezor; Luret A Lar; Michael A Igbe; Ramatu A Abdullahi; Monsuru A Adeleke; Oluwatosin B Adekeye; Elizabeth O Elhassan (PLoS Neglected Tropical Diseases)
Background Onchocerciasis caused by the filarial parasite Onchocerca volvulus and transmitted by Simulium damnosum s.l. remains a public health concern in Nigeria. Infestation of S. damnosum s.l. along rivers Gurara and Kaduna; and heavy intensity of O. volvulus infection in Kaduna were documented in 1956. Control of onchocerciasis in Kaduna started 1954 with larviciding using dichlorodiphenyltrichloroethane reduced S. damnosum s.l. population by 94% in 1966. Diethylcarbamazine used for human treatment was discontinued due to toxicity. Kaduna State Ministry of Health and its partners built on this achievement; used annual mass administration of ivermectin consistently between 1989 and 2017 which led to interruption of onchocerciasis transmission in 2018. This study investigated possibility of recrudescence of onchocerciasis with the hypothesis that insecurity-induced migration could cause recrudescence of onchocerciasis. Methodology/principal findings Six out of the 23 Local Government Areas (LGAs) in Kaduna State were selected for evaluation. Adult S. damnosum s.l. were captured across seven breeding sites using human landing collectors from July to October 2023. Pooled screen assays of 72 pools heads of black flies were conducted using quantitative polymerase chain reaction (qPCR) for O. volvulus detection. Dried blood samples from 3107 children aged 5-9 years were collected; with 1502 samples analysed using alkaline phosphatase enzyme-linked immunosorbent assay due to financial constraints. Twenty pools of the 72 pools of heads (27.8%) of S. damnosum s.l. analysed were positive for O. volvulus in Kagarko and Kachia LGAs (> 1/2000 infective flies; 95% upper confidence limit 0.49) with qPCR prevalence of 0.32%. Two children from security compromised communities tested seropositive (prevalence 0.31%; 95% upper confidence limit 0.317). Conclusion/significance The findings demonstrated ongoing onchocerciasis transmission in Kaduna despite the interruption in 2018. This calls for evaluation of the extent of recrudescence and identification of key drivers such as human migration, fly movement and insecurity.